2019
DOI: 10.4103/ajns.ajns_277_18
|View full text |Cite
|
Sign up to set email alerts
|

A rare chronic presentation of schwannoma with hemorrhage

Abstract: Spinal schwannomas are slow-growing benign tumors arising from the nerves. In the spinal cord, they arise most commonly from cervical and lumbar levels. They are mostly intradural extramedullary (IDEM) accounting for 30% of intradural tumors showing a female preponderance. They are seen occurring between 25 and 50 years of age. Most of these cases show acute presentation as hemorrhage within the tumor with weakness. This is a rare presentation by itself reported by only 12 cases world over. It is even rarer to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Manipulation of the tumor may occasionally induce par aesthesia or 'shocks' in the innervated area [ 5 ]. Notably, schwannomas presenting as extraspinal swellings over the thoracolumbar region are exceedingly rare, adding a unique dimension to their clinical manifestation [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Manipulation of the tumor may occasionally induce par aesthesia or 'shocks' in the innervated area [ 5 ]. Notably, schwannomas presenting as extraspinal swellings over the thoracolumbar region are exceedingly rare, adding a unique dimension to their clinical manifestation [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…These hemorrhagic lesions affect almost equally the cervical spine (24%), 4 , 5 , 8 , 11 , 18 , 25 , 27) the lumbar tract (24%), 7 , 13 , 16 , 17 , 21 , 22 , 28) the thoracic tract (20%), 2 , 6 , 9 , 14 , 19 , 29) and the thoraco-lumbar passage (20%) 10 , 12 , 20 , 22 , 24 , 26) while the thoraco-cervical, 15) the sacral-lumbar tract, 30) and the sacral spine 23) are more rarely involved (12%). Bleeding can occur within the tumor (34%), 6 , 11 , 12 , 17 , 22 , 25 , 26 , 27 , 28 , 30) between the inner layer of the dura mater and the arachnoid mater of the meninges (subdural hematoma: 22%) 4 , 5 , 8 , 9 , 16 , 18 , 19) or into the subarachnoid space (subarachnoid hemorrhage: 16%) 7 , 10 , 20 , 21 , 24) ; multiple sites can also be involved (13%), such as intratumoral bleeding with subdural hematoma 2 , 23 , 29) or subarachnoid hemorrhage. 13) …”
Section: Discussionmentioning
confidence: 99%
“…Schwannomas, also called neurilemmoma are benign tumors which originate from embryonic neural crest cells of the nerve sheath. It has been reported that these tumors usually occur in the fourth to fifth decades with a slightly female preponderance [ 1 ]. Schwannomas can emerge anywhere along the neural network, however, the head, the flexor surfaces of extremities, and the trunk are mainly involved.…”
Section: Introductionmentioning
confidence: 99%